Effect of prehospital notification on acute stroke care: a multicenter study. Issue 1 (December 2016) - Hsieh, Ming-Ju; Tang, Sung-Chun; Chiang, Wen-Chu; Tsai, Li-Kai; Jeng, Jiann-Shing; Ma, Matthew
Abstract Background The sooner thrombolytic therapy is given to acute ischemic stroke patients, the better the outcome. Prehospital notification may shorten the time between hospital arrival and brain computed tomography (door-to-CT) and the door-to-needle (DTN) time. This study investigated the effect of prehospital notification on acute stroke care in an urban city in Taiwan. Methods This retrospective observational study utilized a prospectively collected dataset from patients treated at 9 hospitals and the emergency medical service (EMS) system in Taipei City from September 1, 2012 to December 31, 2014. During the study period, prehospital notification was performed by emergency medical technicians if the patient met the following criteria: (1) positive Cincinnati Prehospital Stroke Scale (CPSS), (2) symptom onset within 3 h, and (3) a sugar pinprick test result ≥ 60 mg/dL. The demographics, final diagnoses, and data associated with stroke for all patients in the prenotification group and for patients diagnosed with acute stroke within 3 h of symptoms onset were prospectively recorded in the stroke registry. The primary outcome was door-to-CT time and the secondary outcome was DTN time. The sensitivity and positive predictive value (PPV) of prehospital notifications and the association between the volume of patients receiving thrombolytic therapy at individual hospitals and DTN time were also evaluated. Results There were 928 patients who presented ≤ 3 h from stroke onset. Among them, 727 (78.3 %) patients were in the prenotification group; of these, more were male, smokers, and presented with severe symptoms, and fewer had a history of prior stroke or cardiac diseases compared to patients in the non-prenotification group. The median door-to-CT time was significantly shorter in the prenotification group than among the non-prenotification group (13 versus 19 min, p  < 0.001). Prenotification was associated with shorter DTN time (63 versus 68 min, p  = 0.138). The sensitivity and PPV of prenotification of stroke were 78.3 % and 78.2 %, respectively. The DTN time demonstrated a significant and highly negative association with the volume of patients receiving thrombolytic therapy (Spearman's correlation coefficient -0.90, p  < 0.001). Discussion In our study, we found prehospital notification was associated with faster door-to-CT scan and shorter DTN time in patients presenting within 3 hours of symptom onset. Such a close collaboration between hospitals and the EMS system gives citizens an in-time emergency care network. Our study revealed that, like in other countries, prehospital notification for stroke patients improved in-hospital stroke care in Taiwan. Our study showed that the sensitivity and PPV of prenotification decisions according to our CPSS-based criteria was comparable with those in other studies. Our study also found that DTN time was shorter in the hospital that treated a greater volume of patients with thrombolytic therapy. A multicenter collaboration program is needed to help those hospitals with relatively lower stroke patient volume to set up interventions that have been proven to improve stroke care. Conclusions Prehospital notification of stroke can significantly shorten door-to-CT time and improve acute stroke care in Taiwan.